Antibiogram and virulence profiling reveals multidrug resistant Staphylococcus aureus as the predominant aetiology of subclinical mastitis in riverine buffaloes. Issue 6 (22nd September 2022) - Hoque, M. Nazmul; Talukder, Anup Kumar; Saha, Otun; Hasan, Mehedi Mahmudul; Sultana, Munawar; Rahman, ANM Aminoor; Das, Ziban Chandra
Abstract: Background: Staphylococcus spp. are the major causal agents of mastitis in dairy animals worldwide leading to profound economic losses and public health threats. Recently, Staphylococcus aureus has emerged as a multidrug resistant and zoonotic pathogen. This study aimed to characterize S. aureus in subclinical mastitis (SCM) milk samples of riverine buffaloes in Bangladesh through antibiogram and virulence gene(s) profiling, and 16S rRNA gene sequencing. Method: We characterized S. aureus in SCM milk samples (N = 500) of riverine buffaloes through antibiogram and virulence gene(s) profiling, and 16S rRNA gene sequencing. Results: Out of 500 milk samples tested, 188 (37.6%) were found positive for SCM. From 188 SCM samples, 291 isolates were obtained with a prevalence of S. aureus in 37.4% (109/291) isolates. Phylogenetic analysis revealed the evolutionary divergence of S. aureus isolates in bubaline SCM milk samples. The antibiogram profiling showed that about 96.0% S. aureus isolates were multidrug resistant (MDR). Notably, 29 and 16 isolates harboured methicillin‐resistant ( mecA ) and panton‐valentine leucocidin ( pvl ) genes, respectively, and 46 plasmid‐bearing isolates were MDR. Nine Staphylococcal enterotoxins (SEs/SEls) including sea (11.9%), sec (7.4%), sed (4.6%), seg (3.7%), and seh (3.7%) were detected with 72.48% toxinotypes comprising a single gene. Conclusion: This study therefore suggests S. aureus as the single‐most aetiology (∼37.0%) of SCM in riverine buffaloes, and emergence of MDR, enterotoxin producing, and virulent S. aureus strains could impose potential threats to animal welfare and public health. Abstract : Graphical abstract showing overview of the subclinical mastitis (SCM) study in buffalo cows. This study aimed to characterized S. aureus in SCM milk samples of riverine buffaloes through antibiogram and virulence gene(s) profiling, and 16S rRNA gene sequencing. Overall, phylogenetically diverse, multidrug resistant (MDR), virulent, enterotoxin producing S. aureus strains were found as the predominant aetiology of SCM in riverine buffalo cows. This study therefore suggested S. aureus as the single‐most aetiology (∼37.0%) of SCM in riverine buffaloes, and emergence of MDR, enterotoxin producing, and virulent S. aureus strains could impose potential threats to animal welfare and public health.